Implementation of two way Quantum Key Distribution protocol with decoy state - Abdul Khir , Mohd Fared; Mohd Zain, Mohd Norzaliman; Bahari, Iskandar; ., Suryadi; Shaari, Sahbudin (Elsevier, 2012)
We report on the first demonstration of a two way Quantum Key Distribution (QKD) protocol with decoy state. The experiment was conducted over free space medium and exhibits a significant increase in the maximum secure distance of a two way QKD protocol specifically the LM05 protocol.